Does Global Warming Worsen Poverty and Inequality? An Updated Review - Hai-Anh H. Dang; Stephane Hallegatte; Trong-Anh Trinh (Global Labor Organization (GLO), 2023)
We offer an updated and comprehensive review of recent studies on the impact of climate change, particularly global warming, on poverty and inequality, paying special attention to data sources as well as empirical methods. While studies consistently find negative impacts of higher temperature on poverty across different geographical regions, with higher vulnerability especially in poorer Sub-Saharan Africa, there is inclusive evidence on climate change impacts on inequality. Further analyzing a recently constructed global database at the subnational unit level derived from official national household income and consumption surveys, we find that temperature change has larger impacts in the short term and more impacts on chronic poverty than transient poverty. The results are robust to different model specifications and measures of chronic poverty and are more pronounced for poorer countries. Our findings offer relevant inputs into current efforts to fight climate change.
Keywords: Q54; I32; O1; 330; Climate change; temperature; poverty; inequality; subnational data